2000
DOI: 10.2458/azu_jrm_v53i1_white
|View full text |Cite
|
Sign up to set email alerts
|

Response of 2 semiarid grasslands to cool-season prescribed fire

Abstract: Woody perennials have invaded semiarid grasslands throughout the Southwestern United States. This invasion was coupled with decreased grass cover and increased runoff and soil erosion. Fire, which was a natural force that shaped and maintained the grasslands, is a management tool that may aid in restoring and maintaining grass cover. However, fire also poses the risk of increasing erosion and further soil degradation because protection afforded by vegetation is reduced immediately after the fire. Using a rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 14 publications
(19 reference statements)
1
7
0
Order By: Relevance
“…Many studies have found that less-costly prescribed fire, in combination with managed grazing and herbicide applications, can effectively reduce mesquite canopy cover and control invasive species for maintenance of local grasslands (Wright and Bailey 1982;Teague et al 2010). In shrubinvaded grasslands of the southwestern United States, prescribed burning treatments have in some cases effectively eliminated mesquite and enhanced grass recovery by resulting in high shrub mortality and reducing competition for shallow soil moisture, eventually reducing erosion loss (Cable 1967;Martin 1983;DeBano et al 1998;White and Loftin 2000;Parmenter 2008;Ravi and D'Odorico 2008). However, it is important to point out that present notions of best management practices might be inadequate for future planning because they draw heavily from our past knowledge.…”
Section: Journal Of Soil and Water Conservationmentioning
confidence: 99%
“…Many studies have found that less-costly prescribed fire, in combination with managed grazing and herbicide applications, can effectively reduce mesquite canopy cover and control invasive species for maintenance of local grasslands (Wright and Bailey 1982;Teague et al 2010). In shrubinvaded grasslands of the southwestern United States, prescribed burning treatments have in some cases effectively eliminated mesquite and enhanced grass recovery by resulting in high shrub mortality and reducing competition for shallow soil moisture, eventually reducing erosion loss (Cable 1967;Martin 1983;DeBano et al 1998;White and Loftin 2000;Parmenter 2008;Ravi and D'Odorico 2008). However, it is important to point out that present notions of best management practices might be inadequate for future planning because they draw heavily from our past knowledge.…”
Section: Journal Of Soil and Water Conservationmentioning
confidence: 99%
“…Soil and vegetation sampling occurred within the middle 60-m by 60-m area within each plot to protect against edge effects. Within each plot, 3 permanently marked 60-m lines were used for vegetation cover and density measurements (White and Loftin 2000). Soils were collected by cover type (shrub, grass, or bare soil) along the 60-m lines.…”
Section: Experimental Designmentioning
confidence: 99%
“…Change in soil microtopography within each runoff collector was monitored using 2 soil erosion bridge locations established within the area of the runoff-sediment collectors prior to the burn (1 bridge location parallel to the top and 1 centered along the side of each collector; see White and Loftin [2000] for bridge description and image). The bridge used in this study has a center reference, which was created by placement of a nail with a receiving dimple beneath the middle hole of the bridge.…”
Section: Soil Microtopographymentioning
confidence: 99%
See 2 more Smart Citations